2014
DOI: 10.1002/cbic.201402488
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Genetics and Function of an Exopolysaccharide Produced by a Bacterium Living within Fungal Hyphae

Abstract: The rice seedling blight fungus Rhizopus microsporus has an unusual symbiosis with a bacterium, Burkholderia rhizoxinica, which lives within the fungal cytosol and produces a potent phytotoxin that causes severe losses in agriculture. To gain insight into symbiosis factors we investigated the endosymbiont's exopolysaccharide (EPS), a secreted matrix that plays pivotal roles in mediating cell-environment interactions. By a combination of homo- and heteronuclear 2D NMR experiments, we elucidated a previously unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The EPS, which contains mannose as a main-component monosaccharide, has been reported only in fungi and yeast. [45][46][47] Mannose has been reported to be a minor component of the EPSs produced by LAB. 44,48,49) In addition, with respect to LAB-derived EPSs having a high mannose content, 46,50,51) the mannose content in the EPS produced by Lb.…”
Section: Discussionmentioning
confidence: 99%
“…The EPS, which contains mannose as a main-component monosaccharide, has been reported only in fungi and yeast. [45][46][47] Mannose has been reported to be a minor component of the EPSs produced by LAB. 44,48,49) In addition, with respect to LAB-derived EPSs having a high mannose content, 46,50,51) the mannose content in the EPS produced by Lb.…”
Section: Discussionmentioning
confidence: 99%
“…For example, EPS mutants of mutualistic Sinorhizobium meliloti and Rhizobium leguminosarum are impaired in their ability to initiate symbiosis with the legume host ( 72 , 73 ). In contrast, EPS mutants of M. rhizoxinica appear to be able to establish symbiosis with the Rm host in liquid culture ( 74 ). However, in our data set, genes encoding all components of the EPS biosynthesis cluster were extremely upregulated (>30-fold) due to physical contact with both nonhost and host, making it difficult to dismiss their role in interaction with fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Only in Gigasporaceae, mixed populations of CaMg and CaGg have been found, being CaMg directly embedded in the cytoplasm and CaGg surrounded by a fungal membrane (Desirò et al ., ; Toomer et al ., ). In R. microsporus , populations of Br or Be live freely in the host cytoplasm, where Br could produce an exopolysaccharide matrix (EPS) that mediate interactions with its fungal environment (Uzum et al ., ). Similarly, Mycoavidus cysteinexigens in M. elongata seems to be surrounded by a tangled complex of membranes, which presumably are not of fungal origin (Uehling et al ., ).…”
Section: Evidence 1: Fungi Contain Diverse and Abundant Microbiotamentioning
confidence: 97%
“…Thanks to the ability of culturing Br and Be separate from its host R. microsporus and the capacity to genetically modify the endobacterium, it has been possible to demonstrate that endobacteria of R. microsporus are the true producers of the toxins ‘Rhizoxin’ and ‘Rhizonin’ (Partida‐Martinez and Hertweck, ; Partida‐Martinez et al ., ), being rhizoxin the chemical weapon used by R. microsporus to attack rice plants and cause disease. Also, it has been shown that bacteria are required for the asexual development of host R. microsporus as discussed above (Partida‐Martinez et al ., ), and several molecular mechanisms that are important for the establishment and maintenance of the symbiosis had been revealed, such as: the importance of the type III secretion system for eliciting asexual development (Lackner et al ., ); the type II secretion systems and the production of chitinase for the active invasion of fungal cells (Moebius et al ., ); the exopolysaccharides (EPS) that may mediate interactions with the fungal environment (Uzum et al ., ); and recently, the implication of diacylglycerol kinase enzymes, which activity modifies the fungal lipid profile, tuning the interaction with endobacteria (Lastovetsky et al ., ).…”
Section: Evidence 3: Microbiotas and Their Hosts Interact And Affect mentioning
confidence: 97%